2014
DOI: 10.1021/ic501163x
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional and Coordination Number Reductions in a Large Family of Lanthanide Tellurite Sulfates

Abstract: Twenty-two new lanthanide tellurite sulfates with five distinct structures, Ln2(Te2O5)(SO4)2 (Ln = La, Ce, Pr, Nd, Sm, Eu, Gd, Tb; LnTeSO-1), Ho3(TeO3)2(SO4)2(OH)(H2O) (LnTeSO-2), Ln2TeO3(SO4)2(H2O)2 (Ln = Dy, Ho, Er; LnTeSO-3), Ln2(Te2O5)(SO4)2 (Ln = Er, Tm, Yb, Lu; LnTeSO-4), and Ln2(Te4O10)(SO4) (Ln = Gd, Dy, Ho, Er, Tm, Yb; LnTeSO-5), have been prepared and characterized. The topologies of LnTeSO-1, LnTeSO-2, LnTeSO-3, LnTeSO-4, and LnTeSO-5 are substantially different with respect to the connectivity betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…In contrast, an unusual case of aliovalent substitution between both the cations and anions in Th IV (VO 3 ) 2 (Se IV O 3 ) and Ln III (VO 3 ) 2 (I V O 3 ) (Ln = Ce, Pr, Nd, Sm, Eu) without architectural alterations was observed . Furthermore, the structural chemistry and resultant properties of 4f-element-bearing materials can be exquisitely controlled since their ionic radii decrease in an extraordinarily systematic way, termed as the lanthanide contraction. The small variations in charge density are capable of inducing phase changes, and such transitions can be utilized as a new strategy for lanthanide separations, as illustrated by Wang et al…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, an unusual case of aliovalent substitution between both the cations and anions in Th IV (VO 3 ) 2 (Se IV O 3 ) and Ln III (VO 3 ) 2 (I V O 3 ) (Ln = Ce, Pr, Nd, Sm, Eu) without architectural alterations was observed . Furthermore, the structural chemistry and resultant properties of 4f-element-bearing materials can be exquisitely controlled since their ionic radii decrease in an extraordinarily systematic way, termed as the lanthanide contraction. The small variations in charge density are capable of inducing phase changes, and such transitions can be utilized as a new strategy for lanthanide separations, as illustrated by Wang et al…”
Section: Introductionmentioning
confidence: 99%
“…Great success has been achieved in the tellurite–sulfate system, as numerous actinides, lanthanides, transition metals, and even heterobimetallic complexes have been synthesized hydrothermally. Examples of these include M­(TeO 3 )­(SO 4 ) (M = Th, Pu), , Ln 2 (Te 2 O 5 )­(SO 4 ) 2 (Ln = La to Lu, except Pm, Dy, and Ho), Ho 3 (TeO 3 ) 2 (SO 4 ) 2 (OH)­(H 2 O), Ln 2 TeO 3 (SO 4 ) 2 (H 2 O) 2 (Ln = Er to Lu), M 3 (TeO 3 )­(SO 4 )­(OH) 2 ·2H 2 O (M = Ni, Co), M 2 (TeO 3 )­(SO 4 )·H 2 O (M = Co, Mn), and Ln 2 M­(TeO 3 ) 2 (SO 4 ) (Ln = Y, Nd to Lu, except Pm; M = Cu, Co, or Zn). Iodate and tellurite anions both adopt trigonal-pyramidal geometries due to the presence of a stereochemically active lone pair of electrons on I/Te centers. Selenium and sulfur belong to the chalcogen group, and their oxyanions SeO 4 2– /SO 4 2– adopt an identical tetrahedral geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, ligands containing both N-and O donors can exhibit great adaptability while coordinated to metal center. [31][32][33][34][35][36] The coordination ability of the 4-hydroxy derivative of dipicolinic acid, that is, 4-hydroxypyridine-2,6-dicarboxylic acid (Chelidamic acid, CA), will be ideal to explore the structural diversity of LnCPs. [37][38][39][40][41] In this work, we report synthesis, structure, optical band gap energy and magnetism of a series of chelidamic acid based lanthanide coordination polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Tellurite anions are known to have high polarizability and form unique structural topologies. Their variable coordination modes are due to the stereoactive lone pair (SALP) of electrons on the Te IV metal centers. ,, Several studies have suggested that the presence of SALP electrons in oxoanion systems is ideal for the formation of cationic materials because they yield highly distorted metal centers with the O atoms pushed off to the sides. , These observations give this system many favorable attributes for the formation of cationic materials. Herein, we report on the hydrothermal preparation and structural elucidation of a new purely inorganic d/f-heterometallic cationic material, [Ag 2 M­(Te 2 O 5 ) 2 ]­SO 4 (M = Ce IV or Th IV ).…”
mentioning
confidence: 99%
“…Tellurium, because of its SALP electrons and polarizability, can form polymeric structures, resulting in highly variable coordination environments. This is due to tellurium’s ability to bind three, four, or five O atoms and form a variety of building units such as 1D chains, 2D sheets, and 3D frameworks. ,, …”
mentioning
confidence: 99%